Implementation of Local Content on Al-Quran Learning in Public Schools - Cahyaningsih Cahyaningsih (Didaktika Religia, 2017)
This article discusses the implementation of local content learning to read al-Quran in public schools. One aspect of religious education that received less attention is the education of reading the Qur'an. In general, parents are more focused on general education, as a first step is to teach and introduce children to the literacy education of the Qur'an. This study is focused on learning materials local content of reading al-Qur'an in State Junior High School (SMPN) 2 Kasembon Malang regency, revealing the purpose of learning, learning methods, and evaluation used. The approach of this study is qualitative and the type of research is a case study, and the location of research in SMPN 2 Kasembon Malang regency. The data were collected by observation, interview and documentation. The results of this study reveals that the material of learning local content to read write al-Qur'an in SMPN 2 Kasembon Malang Regency is the material reading, writing and application of tajwid. The purpose of learning is to produce students who are able to read al-Qur'an according to the rules of tajwid, improve and implement the values contained in the Qur'an, and can face all challenges, obstacles, and changes that arise in the life of the community. Methods used include lecture, reading, writing, memorizing, assignment, modeling, and story. Meanwhile, the evaluation of learning that is used is replication of practice, daily test, assignment, mid semester or semester test.